In situ g-C3N4 self-sacrificial synthesis of a g-C3N4/LaCO3OH heterostructure with strong interfacial charge transfer and separation for photocatalytic NO removal. Issue 3 (18th December 2017) - Wang, Zhenyu; Huang, Yu; Chen, Long; Chen, Meijuan; Cao, Junji; Ho, Wingkei; Lee, Shun Cheng
Abstract : A novel g-C3 N4 /LaCO3 OH heterojunction was controllably fabricated via an in situ self-sacrificial strategy and this strategy was extended to synthesize g-C3 N4 /carbonate compounds. Abstract : Graphitic carbon nitride (g-C3 N4 ) as a metal-free semiconductor photocatalyst has been continually struggling with the high recombination rate of photo-induced charge carriers. Developing a heterostructure is an effective way to suppress the photo-induced e − –h + pair recombination. In this study, a novel heterostructured g-C3 N4 /hierarchical reuleaux triangle LaCO3 OH nanocomposite was controllably fabricated via a one-pot hydrothermal strategy for the first time rather than through the conventional solid state calcination reaction, relying on the dual-functional roles of g-C3 N4 . g-C3 N4, serving as both the structure directing agent and CO3 2− source in the reaction system, significantly influences the morphology engineering of LaCO3 OH. The time-dependent structural evolutions were discussed in detail. The strong interfacial charge transfer and separation are the dominant factors for activity enhancement of g-C3 N4 /LaCO3 OH towards gaseous nitric oxide (NO) degradation under visible light, as confirmed by experimental characterization and density functional theory (DFT) theoretical calculations. Combined with the identification of reaction intermediates and electron spin resonance (ESR) results, the photocatalytic degradation mechanism of NO over the g-C3 N4 /LaCO3 OH heterojunction was proposed. More importantly, this novel self-sacrificial synthesis strategy was successfully extended to synthesize both g-C3 N4 /Bi2 O2 CO3 and g-C3 N4 /SrCO3 composites, indicating that it can serve as a general method to synthesize g-C3 N4 /carbonate compounds.